Atkins' Physical chemistry / P W Atkins, Julio De Paula - Atkins, P W
This volume features a greater emphasis on the molecular view of physical chemistry and a move away from classical thermodynamics. It offers greater explanation and support in mathematics which remains an intrinsic part of physical chemistry.